Functional Stability of Plasminogen Activator Inhibitor-1. (15th October 2014) - Yasar Yildiz, Songul; Kuru, Pinar; Toksoy Oner, Ebru; Agirbasli, Mehmet
Abstract : Plasminogen activator inhibitor-1 (PAI-1) is the main inhibitor of plasminogen activators, such as tissue-type plasminogen activator (t-PA) and urokinase-type plasminogen activator (u-PA), and a major regulator of the fibrinolytic system. PAI-1 plays a pivotal role in acute thrombotic events such as deep vein thrombosis (DVT) and myocardial infarction (MI). The biological effects of PAI-1 extend far beyond thrombosis including its critical role in fibrotic disorders, atherosclerosis, renal and pulmonary fibrosis, type-2 diabetes, and cancer. The conversion of PAI-1 from the active to the latent conformation appears to be unique among serpins in that it occurs spontaneously at a relatively rapid rate. Latency transition is believed to represent a regulatory mechanism, reducing the risk of thrombosis from a prolonged antifibrinolytic action of PAI-1. Thus, relying solely on plasma concentrations of PAI-1 without assessing its function may be misleading in interpreting the role of PAI-1 in many complex diseases. Environmental conditions, interaction with other proteins, mutations, and glycosylation are the main factors that have a significant impact on the stability of the PAI-1 structure. This review provides an overview on the current knowledge on PAI-1 especially importance of PAI-1 level and stability and highlights the potential use of PAI-1 inhibitors for treating cardiovascular disease.